The Role of Music in Young Learners’ Oral Production in English - Daniel Fernando Pérez Niño (Profile: Issues in Teachers' Professional Development)
This article reports on a study conducted at Universidad Nacional de Colombia in the foreign language extension courses. The author shows how young learners who study English in this program can develop their oral production by making and listening to music. The study took place in the first semester of 2009 and followed the qualitative and descriptive approaches to classroom research. The author describes how young learners view music as a ludic tool that will improve their oral performance and how the activities applied by a music teacher help to reinforce the language topics studied in other English classes.